Variability in Fishmeal Nutritional Value in Weaned Pigs and Development of Predictive Equations - Pei Yang; Xiaoyan Su; Bin Li; Junqi Jin; Bing Yu; Jun He; Jie Yu; Quyuan Wang; Huifen Wang; Daiwen Chen; Hui Yan (Animals)
The apparent ileal digestibility (AID) and standardized ileal digestibility (SID) of amino acids, digestible energy (DE), metabolizable energy (ME), and the apparent total tract digestibility (ATTD) of nutrients in 10 fishmeal (FM) samples were evaluated in weaned barrows (Duroc × Landrace × Yorkshire) using two experiments. In Experiment 1, 11 piglets (18.87 ± 0.10 kg) fitted with T-cannulas were randomly allocated to an 11 × 6 Latin-square design with 11 diets (1 nitrogen-free diet and 10 assay diets) and six periods. The AID and SID of all amino acids (AAs) except proline showed significant differences among all FM (p < 0.05). Importantly, the SID of amino acids was positively correlated with key antioxidant markers and immune parameters, and it was negatively correlated with oxidative stress markers (MDA) and pro-inflammatory cytokines (IL-2 and IL-6). In Experiment 2, 11 piglets (18.05 ± 1.15 kg) were assigned to an 11 × 5 Latin-square design with 11 diets (a 96.35% corn diet and 10 assay diets) and five consecutive periods. Significant variations were observed in the DE, ME, and ATTD of dry matter among different FM samples (p < 0.05). Moreover, predictive equations for estimating the SID of lysine, methionine, threonine, and tryptophan, as well as DE and ME, were established using stepwise regression analysis based on the chemical composition of the FM. These findings demonstrate that the nutritional value of FM in nursery pig diets has been underestimated, and this study provides precise data and predictive methods for evaluating the nutritional quality of FM in precision nutrition.